Potential of dietary hemp and cannabinoids to modulate immune response to enhance health and performance in animals: opportunities and challenges - Hassan, Faiz-ul; Liu, Chunjie; Mehboob, Maryam; Bilal, Rana Muhammad; Arain, Muhammad Asif; Siddique, Faisal; Chen, Fengming; Li, Yuying; Zhang, Jingmeng; Shi, Pengjun; Lv, Biguang; Lin, Qian (Frontiers in Immunology, 2023)
Cannabinoids are a group of bioactive compounds abundantly present in Cannabis sativa plant. The active components of cannabis with therapeutic potential are known as cannabinoids. Cannabinoids are divided into three groups: plant-derived cannabinoids (phytocannabinoids), endogenous cannabinoids (endocannabinoids), and synthetic cannabinoids. These compounds play a crucial role in the regulation various physiological processes including the immune modulation by interacting with the endocannabinoid system (A complex cell-signaling system). Cannabinoid receptor type 1 (CB1) stimulates the binding of orexigenic peptides and inhibits the attachment of anorexigenic proteins to hypothalamic neurons in mammals, increasing food intake. Digestibility is unaffected by the presence of any cannabinoids in hemp stubble. Endogenous cannabinoids are also important for the peripheral control of lipid processing in adipose tissue, in addition to their role in the hypothalamus regulation of food intake. Regardless of the kind of synaptic connection or the length of the transmission, endocannabinoids play a crucial role in inhibiting synaptic transmission through a number of mechanisms. Cannabidiol (CBD) mainly influences redox equilibrium through intrinsic mechanisms. Useful effects of cannabinoids in animals have been mentioned e.g., for disorders of the cardiovascular system, pain treatment, disorders of the respiratory system or metabolic disorders. Dietary supplementation of cannabinoids has shown positive effects on health, growth and production performance of small and large animals. Animal fed diet supplemented with hemp seeds (180 g/day) or hemp seed cake (143 g/kg DM) had achieved batter performance without any detrimental effects. But the higher level of hemp or cannabinoid supplementation suppress immune functions and reduce productive performance. With an emphasis on the poultry and ruminants, this review aims to highlight the properties of cannabinoids and their derivatives as well as their significance as a potential feed additive in their diets to improve the immune status and health performance of animals.